Outcome-Based Education Scoring System Utilizing Modular Object-Oriented Dynamic Learning Environment - Ni'mah, Ana Tsalitsatun; Solihin, Firdaus; Sari, Ita Uliyah (LPPM Universitas Trunojoyo Madura, 2023)
The dynamic nature of education necessitates inventive approaches to assessment and evaluation. This study concentrates on formulating a Scoring System aligned with Outcome-Based Education (OBE) principles, utilizing the Modular Object-Oriented Dynamic Learning Environment (MOODLE) platform. OBE prioritizes showcasing specific learning outcomes, cultivating a student-centric approach. The proposed system seeks to improve assessments through a flexible framework accommodating diverse learning objectives, employing a modular and object-oriented design. Integration with MOODLE, a widely-used e-learning platform, explores seamless implementation and user-friendly interaction. The Scoring System aids educators in efficiently evaluating student performance against predefined outcomes, fostering transparency and accountability.Key features include customizable assessments, progress tracking, and timely feedback. The study also examines the system's impact on student engagement, motivation, and overall learning outcomes, contributing valuable insights to innovative assessment methodologies in contemporary education. In conclusion, the research introduces a Scoring System harmonizing OBE principles with MOODLE's flexibility, benefiting educators, students, and institutions. The study's outcomes provide valuable implications for educators and technologists aiming to enhance assessments in the evolving education landscape.